Efektivitas Pelayanan Administrasi Kependudukan melalui Aplikasi KNG (Klampid New Generation) di Kelurahakan Pegirian, Kecamatan Semampir, Kota Surabaya - Krisna Syarif Hidayatulloh; Muhammad Roisul Basyar (CV. Ulil Albab Corp, 2023)
Klampid New Generation (KNG) is an application and an official website owned by the Surabaya City Population and Civil Registry Service. This application is used to make it easier to manage population administration online, including: Public services, namely the validity of deeds, legalization, Updating Population Data, namely unblocking, blank data, removing duplicate data, deleting dead data, red KK, SKPTI, and adding lives, Civil Registration, namely deed (birth, death, legalization of children, divorce, marriage), reprint of deed, reporting abroad (birth, death, divorce, marriage), correction of certificates issued less than 2 years, adoption, etc., Resident Registration, i.e. migration , moving in, moving out, reprinting KK, KIA, splitting KK, updating titles, submitting electronic KTP (lost, damaged, element changes) changing biodata, etc. Events experienced by residents that must be reported because they result in the issuance or change of family card documents, identity cards, and/or include moving in, moving out, changing address, and limited status of residence to permanent residence. In an effort to optimize the use of the KNG application, the Surabaya city government also disciplines the community in population registration or what is commonly called KALIMASADA (Adminduk Aware Environmental Area). The author uses a measurement of effectiveness according to Sutrisno (2007) in (Haqq & Umiyati, 2022) consisting of; (1) Program Understanding, (2) Right on Target, (3) Measurable on time, (4) Measurable goal achievement, (5) Real change.